Estrés laboral y sus factores de riesgo psicosocial (Work stress and psychosocial risk factors) (Estresse no trabalho e fatores psicossociais de risco) - Díaz Naranjo, Diana Lucia (CES Salud Pública, 2011)
La Resolución 2646 de 2008 tiene como objetivo dar los parámetros en la identificación de los riesgos psicosociales en el trabajo, esto como producto del estrés ocupacional, el presente articulo presenta de una forma concisa y entendible para el empleado en general, el significado de los factores de riesgo psicosocial y las repercusiones que estos puedan llegan a tener en su salud. El Ministerio de Protección incluye en la tabla de Enfermedades Profesionales las patologías derivadas por el estrés laboral, y para esto se apoya en el protocolo para la determinación del origen de las patologías derivadas del estrés y en la batería de instrumentos para evaluar los factores de riesgo psicosocial y contribuir en la toma de decisiones a los profesionales laborales en la determinación del origen de las enfermedades derivadas del estrés ya sean estas de origen común o profesional. Para tal caso las empresas deben destinar recursos humanos y económicos para la identificación, evaluación, prevención, intervención y monitoreo de dichos riesgos psicolaborales, es responsabilidad del empleador velar por la salud de sus empleados, el incumplimiento a lo establecido por el Ministerio será objeto de sanción de conformidad con lo dispuesto en los literales a y c del Articulo 91 del Decreto – Ley 1295 de 1994. Abstract: Resolution 2646 of 2008 aims to provide the parameters in the identification of psychosocial risks at work, that as a result of occupational stress, this paper presents a concise and understandable to the employee in general, the meaning of the factors psychosocial risk and the impact that they can come to have on your health. The Ministry of Protection included in the table of occupational diseases and diseases resulting from work stress, and this is supported by the protocol for determining the origin of diseases resulting from stress and battery of instruments to assess risk factors counseling and help in making decisions to the professionals working on determining the origin of stress-related illnesses and whether they are of common origin or professional. For this case, the companies must allocate human and financial resources for the identification, evaluation, prevention, intervention and monitoring of these risks psicolaborales is employer’s responsibility to ensure the health of their employees, failure as determined by the Ministry will be penalty in accordance with the provisions of subparagraphs a and c of Article 91 of Decree - Law 1295 of 1994. Resumo: Resolution 2646 of 2008 aims to provide the parameters in the identification of psychosocial risks at work, that as a result of occupational stress, this paper presents a concise and understandable to the employee in general, the meaning of the factors psychosocial risk and the impact that they can come to have on your health. The Ministry of Protection included in the table of occupational diseases and diseases resulting from work stress, and this is supported by the protocol for determining the origin of diseases resulting from stress and battery of instruments to assess risk factors counseling and help in making decisions to the professionals working on determining the origin of stress-related illnesses and whether they are of common origin or professional. For this case, the companies must allocate human and financial resources for the identification, evaluation, prevention, intervention and monitoring of these risks psicolaborales is employer’s responsibility to ensure the health of their employees, failure as determined by the Ministry will be penalty in accordance with the provisions of subparagraphs a and c of Article 91 of Decree - Law 1295 of 1994.